IMPACT OF SOCIAL MEDIA ON SOCIAL CAPITAL AND EMPLOYEES’ WORK PERFORMANCE: EVIDENCE FROM PAKISTAN BANKING SECTOR (Contemporary Journal of Social Science Review, 2025)
In this era, social media are important for sharing information. The widespread use of social media has created a great opportunity for organizations' employees to collaborate with colleagues, exchange work-related information, and share personal experiences. This study aims to explore the effective use of social media in the workplace. Specifically, the present study identifies the effect of the Norm of reciprocity, Shared Vision, Trust, and Social Interaction Ties, on knowledge donating and knowledge collecting. knowledge donating and knowledge collecting affect employees’ work performance. The survey study was conducted and the data was collected through an online Google form. In this research, the sample size was 367, and the unit of analysis was the employees who use social media in the banking sector. Two software were used for data analysis SPSS and Smart Pls. In this current research, the SPSS used for the demographics variable and smart-pls was used for Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study found that the Norm of reciprocity, Shared Vision, Trust, and Social Interaction Ties, a positive significant effect on knowledge donating and knowledge collecting. knowledge donating and knowledge collecting has a positive significant effect on employees’ work performance. Notable; the primary objective is to gain valuable insights into the banking sector employees, for sharing work-related information.